Exchange of Laptev Sea and Arctic Ocean halocline waters in response to atmospheric forcing. - Bauch, Dorothea; Dmitrenko, Igor; Wegner, Carolyn; Hölemann, Jens A; Kirillov, Sergey A; Timokhov, Leonid; Kassens, Heidemarie (PANGAEA, 2009)
Combined d18O/salinity data reveal a distinctive water mass generated during winter sea ice formation which is found predominantly in the coastal polynya region of the southern Laptev Sea. Export of the brine-enriched bottom water shows interannual variability in correlation with atmospheric conditions. Summer anticyclonic circulation is favoring an offshore transport of river water at the surface as well as a pronounced signal of brine-enriched waters at about 50 m water depth at the shelf break. Summer cyclonic atmospheric circulation favors onshore or an eastward, alongshore water transport, and at the shelf break the river water fraction is reduced and the pronounced brine signal is missing, while on the middle Laptev Sea shelf, brine-enriched waters are found in high proportions. Residence times of bottom and subsurface waters on the shelf may thereby vary considerably: an export of shelf waters to the Arctic Ocean halocline might be shut down or strongly reduced during "onshore" cyclonic atmospheric circulation, while with "offshore" anticyclonic atmospheric circulation, brine waters are exported and residence times may be as short as 1 year only.
Physical oceanography and hydrochemistry from the Laptev Sea, Arctic Ocean
Keywords: ARK-XIV/1b; CTD/Rosette; CTD-RO; East Siberian Sea; Giant box corer; GKG; Helicopter; IK03-01-A; IK03-02-A; IK03-03-A; IK03-03-B; IK03-04-A; IK03-05-A; IK03-06-A; IK03-07-A; IK03-08-A; IK03-09-A; IK03-10-A; IK03-11-A; IK03-12-A; IK03-13-A; IK03-14-A; IK03-15-A; IK03-16-A; IK03-17-A; IK03-18-A; IK03-19-A; IK03-20-A; IK03-21-A; IK03-22-A; IK03-23-A; IK93_1; IK93_10; IK93_100; IK93_101; IK93_102; IK93_103; IK93_104; IK93_105; IK93_106; IK93_107; IK93_108; IK93_109; IK93_11; IK93_110; IK93_111; IK93_112; IK93_113; IK93_114; IK93_115; IK93_116; IK93_117; IK93_118; IK93_119; IK93_12; IK93_120; IK93_121; IK93_122; IK93_123; IK93_124; IK93_125; IK93_126; IK93_127; IK93_128; IK93_129; IK93_13; IK93_130; IK93_131; IK93_14; IK93_15; IK93_16; IK93_17; IK93_18; IK93_19; IK93_2; IK93_20; IK93_21; IK93_22; IK93_23; IK93_24; IK93_25; IK93_26; IK93_27; IK93_28; IK93_29; IK93_3; IK93_30; IK93_31; IK93_32; IK93_33; IK93_34; IK93_35; IK93_36; IK93_37; IK93_38; IK93_38a; IK93_39; IK93_4; IK93_40; IK93_41